A new approach to design control engineering lectures: an example for hybrid systems - Gambier, Adrián (IFAC Proceedings Volumes, 2016)
In this contribution, a new approach to design lectures using active learning is proposed. It is based on the constructivist learning cycle model, which is implemented by using a sandwich structure. Moreover, the evaluation is carried out by means of portfolio assessment. Finally, the whole concept is applied to an introductory lecture on modelling of hybrid systems as an illustrative example.